Soluzioni di Machine Learning per il Patrimonio Culturale. Il progetto ArtI4EO. - Solutions, Nais (Archeomatica, 2025)
Through ArtI4EO, the Project Team wanted to explore the possible use of neural networks based on ML techniques applied to satellite, photographic and UAV image datasets, i) for a more in-depth description of the context in which an archaeological asset is located and ii) for the characterization of some types of damage present on the surface of the assets. The use of Machine Learning and Deep Learning techniques in the context of monitoring and safeguarding cultural heritage constitutes an important technological advancement. In particular, having automatic tools and methodologies for identifying damage constitutes a strategic asset of considerable importance, especially if applied to the Italian context characterized by an incredible widespread archaeological and architectural heritage.